2002
DOI: 10.1136/jech.56.10.766
|View full text |Cite|
|
Sign up to set email alerts
|

Suicide and political regime in New South Wales and Australia during the 20th century

Abstract: Study objective: Australia has had a two party parliamentary political system for most of the period since its Federation in 1901, dominated either by a social democratic (Labor) or a conservative ideological perspective. This paper investigates whether such political differences at Federal and State levels have influenced suicide rates in the state of New South Wales (NSW) for the period 1901-1998. Design: Federal government type, NSW State government type, and combinations of both Federal and NSW State gover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 49 publications
3
32
2
Order By: Relevance
“…Our results are broadly consistent with data from other studies of suicide and climate, notably that of Nicholls et al (2), and the results in males reported by Page et al (5). We found distinct age, sex, regional, and long-term time trends in suicide rates with increased risk associated with spring and a smaller association with above-average maximum temperatures.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results are broadly consistent with data from other studies of suicide and climate, notably that of Nicholls et al (2), and the results in males reported by Page et al (5). We found distinct age, sex, regional, and long-term time trends in suicide rates with increased risk associated with spring and a smaller association with above-average maximum temperatures.…”
Section: Discussionsupporting
confidence: 93%
“…That study focused on the association of conservative government and suicide (5). The authors argued that conservative administrations placed greater stress on individualism, diminishing social capital and enhancing the risk of suicide in vulnerable individuals.…”
mentioning
confidence: 99%
“…The majority of studies from Europe used data from countries that have relatively stronger social welfare systems that may mitigate the effects of poverty and associated factors. Our data is consistent with compelling but inconclusive evidence of between-and within-country examinations of the effects of government policies on suicide rates (Bhatia et al 1987;Blakely & Collings, 2002 ;Page et al 2002 ;Shaw et al 2002 ;Stack, 2002).…”
Section: Region Of Datasupporting
confidence: 90%
“…From 2007-2013, there was socialist national government in Australia, and a stable socialist state government in Queensland throughout [2003][2004][2005][2006][2007][2008][2009][2010][2011][2012]. Evidence exists to suggest that socialist governments may lower suicide rates [53,54].…”
Section: Discussionmentioning
confidence: 99%